2020
DOI: 10.1073/pnas.2005087117
|View full text |Cite
|
Sign up to set email alerts
|

A goal-driven modular neural network predicts parietofrontal neural dynamics during grasping

Abstract: One of the primary ways we interact with the world is using our hands. In macaques, the circuit spanning the anterior intraparietal area, the hand area of the ventral premotor cortex, and the primary motor cortex is necessary for transforming visual information into grasping movements. However, no comprehensive model exists that links all steps of processing from vision to action. We hypothesized that a recurrent neural network mimicking the modular structure of the anatomical circuit and trained to use visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 67 publications
(82 reference statements)
0
84
0
Order By: Relevance
“…repertoire. Importantly, recent simultaneous recordings from multiple areas in animal models and the application of dynamical system frameworks to the analysis of neuronal populations data [82,83] greatly contributed to elucidate the visuomotor transformations underlying the identification and selection of object features relevant for action planning and execution [20,84]; these approaches will likely play an important role in deciphering the neural and computational principles underlying social affordance processing in different contexts (see Outstanding Questions).…”
Section: Open Accessmentioning
confidence: 99%
“…repertoire. Importantly, recent simultaneous recordings from multiple areas in animal models and the application of dynamical system frameworks to the analysis of neuronal populations data [82,83] greatly contributed to elucidate the visuomotor transformations underlying the identification and selection of object features relevant for action planning and execution [20,84]; these approaches will likely play an important role in deciphering the neural and computational principles underlying social affordance processing in different contexts (see Outstanding Questions).…”
Section: Open Accessmentioning
confidence: 99%
“…This approach can be divided into two steps: (1) building network models to reproduce intact behavior (forward engineering) and (2) 'breaking' the model to analyze the internal structure and emulate the motor impairments and recovery processes (reverse engineering). Michaels et al (2020) showed that the inhibition of a part of hierarchical RNNs showed unique patterns of motor deficits similar to those observed in animal experiments [69]. Other studies also demonstrated that deactivation of brain areas could be emulated by the deactivation of motor control models, such as the optimal feedback control model [70,71].…”
Section: Future Direction To Understand the Neural Mechanisms For Hyper-adaptabilitymentioning
confidence: 63%
“…Utilizing multiple areas in RNNs is technically straightforward and commonplace in machine learning [28,29]. In neuroscience, multi-area RNNs models are increasingly being used to address specific questions about how different circuits in the brain interact [30][31][32][33][34]. The main challenge is to have different model areas meaningfully map onto actual brain areas.…”
Section: Figure 1 Multi-area Rnns A)mentioning
confidence: 99%
“…Another approach is based on area-specific connectivity. For example, one can build a hierarchy of RNNs, where the first area preferentially targets the second, and so on, similar to hierarchical models of the sensory systems (Fig 1c) [30,32]. In a hierarchical RNN, modules lower on the hierarchy will have representation/dynamics resembling more the (sensory) inputs, while those higher along the hierarchy will have representations more closely related to the (motor) outputs [30].…”
Section: Figure 1 Multi-area Rnns A)mentioning
confidence: 99%